PERENCANAAN TATA LETAK FASILITAS PADA PRODUK TROLLEY - Ade Astuti Widi Rahayu; Aris Insan Waluya; Ragil Yuli Santosa; Abu Jaelani; Fajar Maulana Sodik; Nunu Nugraha; Rizky Jaenudin (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2020)
Layout is one of the most important things in a company in designing the needs and facilities that support a business and production process. The purpose of this study was to make a facility layout plan for the trolley assembly practicum at the Production and Manufacturing Systems Laboratory, Universitas Buana Perjuangan Karawang. The method used in this study uses the blocplan algorithm analysis method. Based on the results of the research that has been carried out, making part drawings and operation process charts are used to obtain an accurate and unambiguous description of the geometric features of a component and obtain an overview of the plant layout requirements obtained based on the needs of raw materials, machines, and the efficiency of each operating process and examination, while activity relationship chart analysis, blocplan algorithm analysis and area allocation diagram analysis were used to determine a detailed description or layout template for factory facilities in the hope of optimizing productivity and reducing company losses.